Students’ Elementary Literacy Skill And Critical Thinking Skill Supported By School Literacy Program (SLP) - Sri Dewi Nirmala; R. Rahman; B. Musthafa (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
The literacy skills of elementary school students in Indonesia, according tointernational instructional survey data such as PISA and PIRLS are generally atlow ability level. Starting from this condition, the government then launched theSchool Literacy Program (SLP) which is in sync with the implementation ofCurriculum 2013. This study aims to analyze and calculate the difference ofliteracy ability and students’ fourth graders critical thinking in schools thatorganize SLP in three areas of the village, transitions, and cities located inSukabumi Indonesia. The results showed that the students' fourth-grade literacyability at the SLP organizing school was at a low level of 66.89, the middle level55, the high level 54.67, and the advanced level of 55.89. The students' criticalthinking ability is at a low level of 82.94, 55.33 and 55.67. Based on the resultsof this study, it can be concluded that fourth graders students’ literacy ability atschool organizer SLP in Sukabumi is at low level / factual literal. While fourthgraders students’ critical thinking was able to reach low levels.